2017
DOI: 10.1002/2017jd026855
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Structure of Extreme Optical Lightning Flashes

Abstract: This study documents the composition, morphology, and motion of extreme optical lightning flashes observed by the Lightning Imaging Sensor (LIS). The furthest separation of LIS events (groups) in any flash is 135 km (89 km), the flash with the largest footprint had an illuminated area of 10,604 km2, and the most dendritic flash has 234 visible branches. The longest‐duration convective LIS flash lasted 28 s and is overgrouped and not physical. The longest‐duration convective‐to‐stratiform propagating flash last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(112 citation statements)
references
References 18 publications
(34 reference statements)
4
105
0
Order By: Relevance
“…As a result, then the flash footprint will be significantly wider (tangentially) than it is long (radially). The top LIS flash in terms of event separation from Figure 4 in Peterson, Rudlosky, et al () shows this exact case where the flash footprint even curves around the edge of the convective feature.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…As a result, then the flash footprint will be significantly wider (tangentially) than it is long (radially). The top LIS flash in terms of event separation from Figure 4 in Peterson, Rudlosky, et al () shows this exact case where the flash footprint even curves around the edge of the convective feature.…”
Section: Resultsmentioning
confidence: 81%
“…This structure describes 30% of all flashes. All of the complex flashes with extreme branch counts from Peterson, Rudlosky, et al () were propagating flashes. Of these, only 4.5% contain a single branch (Figure d) while 4 in 10 contain 20 or more branches.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The qualitative meteorological interpretation suggested that lightning in the trailing, more stratified clouds to the rear of the convective line was larger. Utilizing LIS data, Peterson et al () and Peterson et al () introduced the idea of propagating flashes and suggested that they were a separate class of discharge where group centroids moved in a preferential direction away from the first group so as to elongate the flash footprint. They also diagnosed another class of very bright flash with large illuminated area, so‐called “superbolts,” in which the group centroids did not propagate.…”
Section: Example: a Mesoscale Convective System In Argentinamentioning
confidence: 99%